Nutritional and Management Strategies to Improve Reproductive Performance in Sheep and Goats: A Review - Baker, Ahmed Gh. (American Journal of Biology and Natural Sciences, 2025)
Reproduction represents a major factor influencing productivity and profitability across the sheep and goat industries. Since multiple factors such as nutrition, management, environmental and genetic factors are involved in fertility outcome, unbalanced nutrition and mismanagement are a cause of low ewe conception rate and low progeny survival, which will result in significant economic losses. The review here presents a summary of current information on nutrition-related variables including energy and protein density, vitamins (vitamin A and vitamin E), some antioxidant agents (for example selenium or zinc), fatty acids (i.e., omega-3 and omega-6), and efficient natural phytogenic additives on farm animals reproduction. Management practices covered include flushing, control of the breeding season, nutritional management of the pregnant and lactating ewe, flock health programs, and reproductive technologies like AI. Management and nutritional strategies applied synergistically lead to increased ovulation rate, concept ion, twinning rate, lactation use efficiency and the productive life of farm flocks of sheep. Then, in the main text, we briefly touch on the precision nutrition, biotechnology, and climate-smart farming that comprise potential means for the sheep industry to meet the challenges of climate change and potential feed resource shortage in the future. Together these add on to increased reproductive performance as well as the sustainable in the long run adaptability of production systems for small ruminants to (economic) stresses.